The continuing search for women's emancipation: Perspectives from Begum Rokeya to Arundhati Roy - Ilahi, Adil (Yayasan Mitra Persada Nusantara, 2024)
This study examines the perspectives of Begum Rokeya and Arundhati Roy on women's emancipation, analysing their literary contributions to the discourse on gender equality. The objective is to compare their views on women's freedom and assess how their works reflect and critique contemporary societal conditions. While both authors have passionately advocated for women's liberation, their ideas have not been thoroughly analysed in relation to the present-day struggles of women. This review seeks to bridge that gap by critically evaluating their works in the context of ongoing gender inequalities. The study adopts a qualitative approach, utilizing a comparative textual analysis of Begum Rokeya’s Sultana’s Dream and Arundhati Roy’s The God of Small Things as primary sources. Relevant scholarly articles and feminist theoretical frameworks supplement the analysis, providing a broader understanding of their perspectives on women's rights. Findings reveal that Begum Rokeya’s visionary advocacy for women’s independence, as portrayed in Sultana’s Dream, remains largely unrealized in contemporary society. Despite her utopian vision of a world where women hold power, gender-based oppression persists. Arundhati Roy’s The God of Small Things further highlights the entrenched patriarchal structures and socio-cultural barriers that continue to limit women's autonomy. The comparative analysis underscores the enduring challenges women face and the necessity for sustained efforts toward gender equality. By juxtaposing the works of these two influential authors, this study emphasizes the persistent struggles for women’s rights and the ongoing need for advocacy and reform. The insights drawn from their literary contributions reinforce the urgency of addressing gender disparities and striving for a more equitable society.